PRINCIPLES OF ANTIBIOTIC TREATMENT OF OUT-OF-HOSPITAL UPPER RESPIRATORY TRACT INFECTIONS IN CHILDREN - A. L. Zaplatnikov; N. V. Koroid; A. A. Girina; I. V. Neyman ("Paediatrician" Publishers LLC, 2012)
Special features of etiology of respiratory tract bacterial infections in children in depending of localization of involvement are analyzed in this study. In the article the main principles of rational antibacterial therapy of infectious and inflammatory diseases of respiratory tract in paediatrician practice are discussed. The authors offer the algorithms of first-line antibiotics choosing according to various entities of upper and lower respiratory tract infections in children. There are also suggested the regimens of antibacterial agents dosing in out-patient clinics in children with bacterial respiratory infections.